Speaking with Ghosts that Rob Graves: Traces of Neurasthenia in Robert Graves War Poetry Through a Veteran’s Perspective - Phinazee, Brian C. (My University, 2020)
My purpose of this thesis is to contribute to the ongoing scholarly discussion of Robert Graves and how the effects of neurasthenia can be found within his war poetry. Following Dr. Carl Leggo’s methods and suggestions, I will use the process of deconstruction by utilizing my research sources combined with my own experiences to provide a new, veteran’s perspective. Considering the long career that Robert Graves was able to enjoy before his death, one may even be able to argue that it was the conditions and experiences from his time in the military which set Graves apart and allowed him to maintain relevance until his passing. Keywords: Robert Graves; Neurasthenia; War Poetry; WWI; Deconstruction; Analysis of poetry;
Chapter I: Introduction 1 -- Review of Literature 5 -- The Great War 9 -- Robert Graves 11 -- Neurasthenia 21 -- Neurasthenic Graves 31 -- Deconstructing Poetry like Leggo 38 -- Chapter II: Beating “A Dead Boche” 43 -- Chapter III: Understanding “Not Dead” 69 -- Chapter IV: Conclusion 95 -- BIBLIOGRAPHY 97 -- Bibliography of Images 104 -- APPENDIX A: Complete visual references for the poems used for this thesis 105 -- APPENDIX B: Personally-owned pictures from my time in Iraq, 2006 108.
Keywords: Academic theses; Deconstruction; Graves, Robert, 1895-1985; Neurasthenia; Poetry--Study and teaching; Poetry; War poetry; War poetry, English; World War (1914-1918)